Legal Analysis of the Modus Operandi of Terrorism Funding Under the Guise of Charity: Analisis Hukum Terhadap Modus Operandi Pendanaan Terorisme Berkedok Amal - Muhammad Haidar Ghoni; Ali Masyhar (Universitas Negeri Semarang, 2025)
Terrorist funding is an important part of a series of terrorist acts. Various methods are used by terrorist groups to obtain funds as an effort to continue to exist to spread radicalism and carry out acts of terror. According to data, the population in Indonesia has a high level of generosity in the world, this makes terrorist groups take advantage of opportunities by using the guise of charity by using non-profit organizations (NPOs) to obtain funds with structured methods and without using violence. This study aims to analyze the mode used by NPOs in carrying out the guise of charity as a medium for collecting funds and the form of formulation for eradicating terrorism funding that has been taken by the government, as well as to evaluate the effectiveness of these policies and actions in the national context. This study uses a normative legal research method with a statute approach. This study emphasizes the aspect of fundraising carried out by NPOs in a series of terrorism funding activities. The Indonesian government must always control NPOs by coordinating with related institutions. This is a step in overcoming terrorism funding under the guise of charity in order to create safe and responsible fundraising activities which will be explained in this study.